Correction: Wang et al. Super-Dispersed Fe–N Sites Embedded into Porous Graphitic Carbon for ORR: Size, Composition and Activity Control. Nanomaterials 2021, 11, 2106 - Xin Yu Wang; Ze Wei Lin; Yan Qing Jiao; Jian Cong Liu; Rui Hong Wang (Nanomaterials)
In the original publication [...]